Disclosure Prominence and the Quality of Non‐GAAP Earnings - CHEN, JASON V.; GEE, KURT H.; NEILSON, JED J. (Journal of Accounting Research, 2021)
ABSTRACT The SEC prohibits the presentation of non‐GAAP measures before corresponding GAAP measures; however, a large proportion of non‐GAAP reporters present non‐GAAP EPS before GAAP EPS in their earnings announcements. This noncompliance raises questions about whether firms use prominence to highlight higher or lower quality non‐GAAP information. For firms reporting non‐GAAP EPS between 2003 and 2016, prominent non‐GAAP EPS is associated with higher quality non‐GAAP reporting. Further tests reveal that nonregulatory incentives, rather than regulatory costs, explain this relation. Specifically, prominence is associated with higher quality non‐GAAP reporting in settings where prominence is not regulated, investors ignore prominence when non‐GAAP reporting quality is lower, and the minority of firms using prominence to mislead exhibit characteristics associated with weaker investor monitoring. Overall, we provide evidence that regulatory noncompliance can reflect an intent to inform, and that most firms use prominence to highlight higher quality non‐GAAP information despite prohibitive regulation.